Pengembangan Buku Monitoring Deteksi Kesehatan Ginjal pada Penderita Diabetes Melitus - Susanti, Eva; Jawiah, Jawiah; Kosasih, Cecep Eli (Journal of Telenursing (JOTING), 2024)
This study aims to develop a kidney care monitoring book for Diabetes Mellitus patients in the working areas of several Health Centers in Ogan Ilir Regency, South Sumatra. The method used is the research and development method with a descriptive research type. Limited trials were conducted in the working areas of several Health Centers in Ogan Ilir Regency, South Sumatra. The instruments used were validation questionnaires and assessment questionnaires for the feasibility of the Monitoring book by material experts and media experts. Data analysis used a Likert scale that was expressed as a percentage to determine the level of feasibility of the monitoring book. The results of the study showed that the product trial was conducted by two experts, namely material experts and media experts. Material experts with a very valid category with a feasibility percentage of 93.33% and media experts with a very valid category with a feasibility percentage of 92.30%. So that the product is feasible for small-scale trials, conclusion, Based on the feasibility test by material experts and media experts, the kidney care monitoring book is declared feasible to be continued in small-scale trials. Keywords: Kidney Care Monitoring Book, Diabetes Mellitus, Kidney